Preparation method of ZnFe2O4 wave-absorbing material
The preparation of ZnFe2O4 absorbing materials through high-temperature mechanical force chemistry has solved the problems of complex preparation process and uncontrollable particle size of existing ferrite absorbing materials, and achieved simple process, low energy consumption and uniform particle size distribution, and had excellent absorbing performance.
Patent Information
- Application Number
- CN202510026936.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-25
AI Technical Summary
The existing preparation methods of ferrite absorbing materials have problems such as low yield, complex process and uncontrollable particle size, and the absorption frequency band is narrow and the absorption intensity is limited.
The ZnFe2O4 absorbing material was prepared by high-temperature mechanical force chemistry. By mixing zinc oxide powder and iron trioxide powder and performing high-temperature ball milling in a ball mill, a ZnFe2O4 material with uniform particle size distribution and excellent absorbing properties was obtained.
The preparation of ZnFe2O4 absorbing materials with simple process, low energy consumption and uniform particle size distribution is achieved, and has excellent absorbing performance, especially in the 2.8-5.5GHz frequency band, it has efficient electromagnetic wave absorption capacity.
Smart Images

Figure CN119873899A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wave absorbing materials, and in particular to a method for preparing a ZnFe2O4 wave absorbing material. Background Art
[0002] Ferrite is one of the most mature absorbing materials currently studied. Its preparation methods mainly include hydrothermal method, solvothermal method, sol-gel method, coprecipitation method and solid phase sintering method, etc. These methods can successfully prepare ferrite with excellent absorbing properties. Among them, the hydrothermal method can synthesize ferrite particles with high purity and uniform particle size at a relatively low temperature, but the reaction conditions are relatively harsh and the product yield is relatively low; the solvothermal method can react in a non-aqueous medium and is suitable for the preparation of various types of precursor materials. The morphology of the product can be controlled by adjusting the type of solvent and the reaction conditions, but high temperature and high pressure reaction conditions are required, and the repeatability and controllability of the product are poor; the sol-gel method can be carried out under relatively mild conditions, and it is easy to achieve doping and modification; the product has high purity and uniformity, but the process is relatively long and requires drying, calcination and other processes. The coprecipitation method is simple to operate, low-cost, and suitable for large-scale production. The composition and morphology of the product can be adjusted by controlling the pH value and reaction temperature, but the control of the particle size and morphology is relatively poor, and it is difficult to obtain monodisperse particles. The product may agglomerate. The solid-phase sintering method is mature and easy to industrialize. The performance of the product can be controlled by adjusting the raw material ratio and sintering temperature, but it requires high-temperature sintering, which consumes a lot of energy. The sintering temperature between particles is difficult to control, which may lead to uneven porosity of the product, thereby affecting the absorption performance. Therefore, the current preparation methods all have problems such as low yield, complicated process and uncontrollable product particle size. In addition to the above problems, there are also performance problems such as narrow absorption band and limited absorption intensity. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a ZnFe2O4 absorbing material to solve the problems of the above-mentioned ferrite absorbing material having a complicated preparation process, uncontrollable product particle size and poor performance.
[0004] To achieve the above object, the present invention provides a method for preparing a ZnFe2O4 absorbing material, comprising the following steps:
[0005] (1) mixing zinc oxide powder and ferric oxide powder to obtain a mixed powder;
[0006] (2) The mixed powder and grinding balls are added into a ball milling jar, and then loaded into a high-temperature energy ball mill for ball milling. After the ball milling is completed, the ZnFe2O4 absorbing material is obtained.
[0007] Preferably, in step (1), the molar ratio of zinc oxide powder to ferric oxide powder is 1:(2-2.2).
[0008] Preferably, the grinding balls in step (2) are zirconia grinding balls, and the zirconia grinding balls include zirconia grinding balls with a diameter of 8 mm and zirconia grinding balls with a diameter of 16 mm in a mass ratio of 1:(2-2.5).
[0009] Preferably, in step (2), the mass ratio of the mixed powder to the grinding balls is 1:(5-20).
[0010] Preferably, the ball mill in step (2) is made of 2520 stainless steel, with an inner diameter of 165 mm, an outer diameter of 170 mm, and a height of 150 mm.
[0011] Preferably, in step (2), the ball milling temperature is 773-1023K, and the heating rate is 4K·min -1 , the rotation speed is 30~50rpm.
[0012] Preferably, the ball milling time in step (2) is 4 to 12 hours.
[0013] Therefore, the present invention adopts a method for preparing a ZnFe2O4 absorbing material with the above structure, which has the following beneficial effects:
[0014] (1) The present invention uses a high-temperature mechanochemical method to prepare ZnFe2O4, which has the characteristics of simple process, low energy consumption, uniform product particle size distribution and large-scale production. The prepared ZnFe2O4 can be used as an absorbing material.
[0015] (2) The ZnFe2O4 prepared by the present invention is spherical and has a spinel structure, and the saturation magnetization is 44.94emu / g. Under the process conditions of ball milling temperature of 973K, ball milling time of 10h and ball-to-material ratio of 15:1, the product has the best wave absorption performance. At this time, the minimum reflection loss of the sample is -26.0dB (corresponding to 99.7488% electromagnetic wave absorption rate) when the matching thickness is 7.6mm, and the effective absorption band covers 2.8-5.5GHz.
[0016] (3) The excellent wave absorbing performance of the ZnFe2O4 material prepared in the present invention can be attributed to the strong polarization relaxation effect of the sample in the medium and high frequency bands. At the same time, the magnetic loss mechanism is the synergistic effect of eddy current loss and natural resonance, so it has a strong electromagnetic wave attenuation ability and better impedance matching characteristics within 2-18 GHz.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1Schematic diagram of the preparation process of the ZnFe2O4 absorbing material of the present invention;
[0019] Figure 2 XRD patterns of the products at different temperatures;
[0020] Figure 3 SEM images of the products at different temperatures;
[0021] Figure 4 It is the hysteresis loop diagram of the product at different temperatures;
[0022] Figure 5 It is the relationship between the electromagnetic parameters and frequency of the product at different temperatures;
[0023] Figure 6 It is the three-dimensional reflection loss diagram of the product at different temperatures;
[0024] Figure 7 The relationship curve between the reflection loss and frequency of the product at different temperatures and a specific matching thickness;
[0025] Figure 8 is the three-dimensional Cole-Cole curve of the product at different temperatures;
[0026] Fig. 9 The relationship between the C0 value of the product at different temperatures and the frequency;
[0027] Fig.10 The attenuation coefficient (α) and impedance matching characteristics (Z) of samples prepared at different temperatures vary with frequency;
[0028] Fig.11 XRD patterns of the products at different ball milling times;
[0029] Fig.12 SEM images of the products at different ball milling times;
[0030] Fig.13 The hysteresis loop diagram of the product at different ball milling times;
[0031] Fig.14 This is the relationship between the electromagnetic parameters and frequency of the product at different ball milling times;
[0032] Fig.15 The three-dimensional reflection loss diagram of the product at different ball milling times;
[0033] Fig.16 The curves are the relationship between the reflection loss and the frequency of the products at different ball milling times at specific matching thickness;
[0034] Fig.17 The three-dimensional Cole-Cole curves of the products at different ball milling times;
[0035] Fig.18 The relationship between the C0 value of the product and the frequency at different ball milling times;
[0036] Fig.19 The attenuation coefficient (α) and impedance matching characteristics (Z) of the samples prepared with different ball milling times vary with frequency;
[0037] Fig. 20 The XRD patterns of the products under different ball-to-material ratios;
[0038] Fig.21 The SEM images of the products under different ball-to-material ratios;
[0039] Fig. 22 It is the hysteresis loop diagram of the product under different ball-to-material ratio;
[0040] Fig.23 This is the relationship between the electromagnetic parameters and frequency of the product under different ball-to-material ratios;
[0041] Fig.24 It is the three-dimensional reflection loss diagram of the product under different ball-to-material ratios;
[0042] Fig.25 It is the relationship curve between the reflection loss and frequency of the products with different ball-to-material ratios at a specific matching thickness;
[0043] Fig.26 It is the three-dimensional Cole-Cole curve of the product under different ball-to-material ratios;
[0044] Fig. 27 The relationship between the C0 value of the product and the frequency under different ball-to-material ratios;
[0045] Fig.28 The attenuation coefficient (α) and impedance matching characteristics (Z) of samples prepared with different ball-to-material ratios vary with frequency. DETAILED DESCRIPTION
[0046] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0047] Example 1
[0048] A method for preparing a ZnFe2O4 absorbing material comprises the following steps:
[0049] like Figure 1As shown, ZnO and Fe2O3 powders are used as raw materials, and ZnO powder and Fe2O3 powder are weighed and mixed evenly according to n(ZnO)∶n(Fe2O3)=1∶2 to obtain a mixed powder, and the total mass of the mixed powder is 100g.
[0050] The mixed powder and zirconium oxide grinding balls (diameters of 8 mm and 16 mm, respectively, mass ratio of 1:2) were placed in a ball mill (2520 stainless steel, inner diameter 165 mm, outer diameter 170 mm, height 150 mm), and then placed in a high-temperature energy ball mill for ball milling to obtain ZnFe2O4 absorbing material. The ball milling temperature was 973K, and the heating rate was 4K·min -1 , the rotation speed was 40 rpm, the ball milling time was 10 h, the ball-to-material ratio was 15:1, and argon gas was introduced for protection during the reaction.
[0051] Example 2
[0052] The difference between this embodiment and embodiment 1 is that the ball milling temperature is different. The ball milling temperature of this embodiment is 823K, 873K, 923K or 1023K.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that the ball milling time is different. The ball milling time of this embodiment is 4h, 6h, 8h or 12h.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 1 is that the ball-to-material ratio is different. The ball-to-material ratio of this embodiment is 5:1, 10:1 or 20:1.
[0057] Comparative Example 1
[0058] The difference between this comparative example and Example 1 is that the preparation method of the ZnFe2O4 absorbing material is different.
[0059] This comparative example provides a method for preparing a ZnFe2O4 absorbing material, which is synthesized by a precursor high temperature sintering method, comprising the following steps:
[0060] Zinc nitrate, ferric nitrate and citric acid powder were weighed in a molar ratio of 1:2:4, and a solution was prepared and ammonia water was added to adjust the pH to 7. The solution was then placed in a 90°C water bath and stirred for 4.5 hours until the liquid was a viscous colloid. The obtained colloid was then placed in a 120°C oven and dried for 4 hours to obtain a dry gel. The dry gel was placed in a muffle furnace and heated to 800°C at a heating rate of 60°C / h. After reacting for 8 hours, the product was naturally cooled to room temperature to obtain ZnFe2O4.
[0061] Comparative Example 2
[0062] The preparation methods of the ZnFe2O4 absorbing materials in this comparative example and Example 1 are different.
[0063] This comparative example provides a method for preparing a ZnFe2O4 absorbing material by a hydrothermal method, comprising the following steps:
[0064] Weigh zinc nitrate and ferric nitrate powder according to the molar ratio of 1:2, and then - / NO3=3 to calculate the mass of NaOH required, and prepare the obtained nitrate and NaOH into corresponding solutions. Use a polytetrafluoroethylene-lined autoclave, set the reaction temperature at 200℃ and keep the reaction for 6 hours. After the reaction is completed, cool to room temperature, use a high-speed centrifuge to wash the sample with water 3 times and alcohol 2 times, respectively, to obtain 7nFe2O4.
[0065] Performance Testing
[0066] According to Bragg's law (Formula 1) and Debye-Scherrer formula (Formula 2), the average grain size, interplanar spacing, unit cell parameters and other information of the sample can be roughly determined through information such as the peak position and the half-height width of the diffraction peak; after obtaining the average grain size information of the sample, the lattice strain coefficient of the sample can be calculated by the modified Williamson-Hall formula (Formula 3).
[0067] 2d sinθ=nλ Formula 1
[0068]
[0069] Wherein, d is the lattice spacing, θ is the angle between the incident X-ray and the crystal plane, λ is the wavelength of the incident wave, D is the average grain size, K is the Scherrer constant (K=0.89), and β is the half-height width of the diffraction peak.
[0070] The phase and crystal structure of the samples were analyzed by X-ray diffraction analyzer (XRD, Cu target Kα ray, scanning rate of 5° / min, scanning angle of 10°-80°). The particle size distribution and morphology of the samples were observed by scanning electron microscope (SEM). The static magnetic properties of the samples at 300K were tested by vibrating sample magnetometer (magnetic field range of -30-30kOe). The electromagnetic parameters (ε′, ε″, μ′, μ″) of the samples in the frequency range of 2-18GHz were tested by vector network analyzer (VNA). Then, Matlab software was used to calculate the three-dimensional reflection loss diagram of the samples and the reflection loss value (R L ), C0 value, attenuation coefficient (α), impedance matching coefficient (Z) and quarter wavelength (λ / 4) curves.
[0071] (1) Characterization results of ZnFe2O4 absorbing materials prepared in Example 1 and Example 2
[0072] In order to explore the effect of temperature changes during the reaction on the product structure, experiments were carried out at 823K, 873K, 923K, 973K and 1023K respectively.
[0073] Figure 2 The XRD patterns of the products at 823K, 873K, 923K, 973K and 1023K are shown in the figure. The crystal planes corresponding to the characteristic peaks are marked in the figure. In addition to the raw materials ZnO and Fe3O4, the phase composition of the product at 823K also contains an incompletely crystallized intermediate phase Fe x Zn y O, indicating that at this temperature, the raw materials are not enough to react completely. When the temperature is increased to 873K, 923K and 973K, the samples obtained all show the Fd3m space group structure. At the same time, there are characteristic peaks of ZnO at 2θ of about 31.86° and 36.26°. This is because under the coupling of high temperature and mechanical force, the local temperature of the contact point between the grinding ball and the reactant particles is too high, causing part of the raw material ZnO to volatilize during the reaction and remain in the product. When the temperature is increased to 1023K, the product is mainly composed of ZnO, Fe3O4 and Fe x Zn y O composition, which is due to the violent collision between the grinding balls and the products, resulting in excessive local temperature and causing the thermal decomposition of ZnFe2O4. The thermal decomposition reaction is as shown in Formula 4: 3ZnFe2O4=3ZnO+2Fe3O4+1 / 2O2.
[0074] Figure 3 The SEM images of the products at 823K, 873K, 923K, 973K and 1023K. As the temperature increases, the agglomeration of the product particles first weakens and then increases. At 823K, the product particles adhere to each other, the boundaries are unclear, and the agglomeration is obvious, indicating that the product crystallization is incomplete at this time, and this temperature is not conducive to the formation of ZnFe2O4. As the temperature increases to 973K, the agglomeration weakens, and the product particles present a nearly spherical structure. As the temperature increases, the particle size of the product first decreases and then increases. Figure 3The particle size distribution diagram in (bc) shows that the average particle size of the product at 873K and 923K is about 0.26μm and 0.27μm respectively, and the particle size is distributed in the range of 0-0.5μm; when the temperature rises to 973K, the particle size of the product decreases, the average particle size is about 0.21μm, the content of small-sized particles increases, and the particle size is distributed in the range of 0-0.4μm; when the temperature rises to 1023K, the particle size of the product increases, the average particle size is about 0.32μm, the content of large-sized particles increases, the particle size is distributed in the range of 0-0.8μm, and there is a certain amount of agglomeration. The increase in particle size is caused by the excessive growth of the product grains due to the high reaction temperature, and the mechanical force increases its surface area and surface energy, which leads to the occurrence of agglomeration.
[0075] Figure 4 is the hysteresis loop diagram of the product at different temperatures, the corresponding M s 、M r and H c As shown in Table 1. The hysteresis loops of the samples at different temperatures all show an "S" shape, indicating that they all have soft magnetic properties. s Increases with increasing temperature. At 823K, M s At 1023K, M increases to 44.87emu / g. s The difference is due to the incomplete crystallization of the product at 823K, and its magnetism mainly comes from Fe3O4 and Fe x Zn y O phase; as the temperature rises to 973K, the crystallinity of the product increases, and the magnetism of the product comes from the ZnFe2O4 particles with good crystallinity; when the temperature is 1023K, the XRD analysis shows that the ZnFe2O4 particles are pyrolyzed, and the magnetism of the product comes from the undecomposed ZnFe2O4 particles, Fe3O4 and Fe x Zn y O phase. Therefore, with the increase of temperature, the type and content of magnetic substances in the product change, affecting its magnetic properties.
[0076] Table 1 Static magnetic properties parameters of samples prepared at different temperatures
[0077] Temperature / K <![CDATA[M s / emu g -1 ]]> <![CDATA[M r / emu g -1 ]]> <![CDATA[H c / You]]> 823 2.53 0.06 33.20 873 2.92 0.08 32.12 923 18.60 0.65 11.31 973 27.08 0.59 17.02 1023 44.94 3.96 74.51
[0078] Figure 5(ab) are ε′ and ε″ of the products at different temperatures. As the temperature increases, both ε′ and ε″ increase. The curves of ε′ all show typical frequency-dependent behavior (the ε′ curve decreases as the frequency increases). The decrease in ε′ is due to the fact that the dipoles inside the material cannot respond quickly to changes in the frequency of the electromagnetic field. When the temperatures are 823K, 873K, 923K, 973K and 1023K, the ε′ values fluctuate in the ranges of 4.08-3.85, 4.51-4.15, 4.90-4.30, 4.74-4.23 and 5.79-4.73, respectively, as the frequency changes. Therefore, as the temperature increases, the electrical storage and electrical loss capabilities of the product are enhanced, and this change may affect its absorbing performance. The reason for the change in ε′ is that when the temperature is too high, the products after the decomposition of some ZnFe2O4 particles enhance the conductivity. In addition, the ε″-f curves of all samples have obvious dielectric resonance peaks in the frequency range of about 6-10 GHz, 12-15 GHz and 16-18 GHz, which comes from the delayed response of the dipole to the alternating electromagnetic field.
[0079] Figure 5 (cd) are μ′ and μ″ of the products at different temperatures. When the temperatures are 823K, 873K, 923K and 1023K, the μ′ values fluctuate between 1.0-1.1, indicating that their magnetic storage capacity is weak; while when the temperature is 973K, the μ′ value is much larger than the μ′ value at other temperatures in the range of 2-5GHz (up to 1.4), fluctuates between 1.0-1.1 in the range of 5-8GHz, and increases to about 1.2 in the range of 8-18GHz, indicating that the sample has the strongest magnetic storage capacity at the temperature of 973K. This difference occurs because the product at 973K has better crystallinity, thus providing excellent magnetic storage capacity. At the same time, with the increase of frequency, the μ″-f curves of all samples decrease in the low frequency band and then remain stable in the high frequency band. This phenomenon can be explained by the Snoek limit. The μ′-f curves and μ″-f curves of all samples show dispersion characteristics in the low frequency range, indicating that there is natural resonance in the samples.
[0080] Figure 5(ef) is the tanδe and tanδm of the products at different temperatures. As the temperature increases, tanδe increases, that is, the dielectric loss capacity increases with the increase of temperature, and the tanδe values of several products are in the range of 0-0.15. By comparing the values of tanδe and tanδm, it can be found that the products at 923K, 973K and 1023K have a tanδm>tanδe value in the range of 2-8GHz, and the difference between the tanδm value and the tanδe value in the range of 8-18GHz is not large, indicating that the loss mechanism of the corresponding product is mainly magnetic loss in the range of 2-8GHz, and the magnetic loss and dielectric loss act together in the range of 8-18GHz. The difference between the tanδm value and the tanδe value of the products at 823K and 873K in the range of 2-18GHz is not large, indicating that the loss mechanism is the joint effect of dielectric loss and magnetic loss. In summary, as the temperature increases, the magnetic loss capacity of the product at low frequency gradually becomes stronger. The loss mechanism is mainly magnetic loss in the low frequency band, and the loss mechanism is the combined effect of dielectric loss and magnetic loss in the medium and high frequency bands.
[0081] Figure 6 is the three-dimensional R of the product at different temperatures L Fig. When the temperature increases from 823K to 973K, R Lmin From -5.2dB to -26.0dB, the corresponding thickness decreases from 9.9mm to 7.6mm. As the temperature continues to rise to 1023K, R Lmin It is -24.2dB, and the corresponding thickness is 10.0mm, indicating that temperature can significantly affect the wave absorbing performance of the product. As the temperature increases, the wave absorbing performance of the product first increases and then decreases. The reason for the difference in wave absorbing performance is that the ZnFe2O4 particles do not reach the crystallization conditions at low temperatures, and there is basically no ZnFe2O4 with wave absorbing ability in the product at this time. The increase in temperature will provide more energy to the reaction system, promote the reaction, and is beneficial to the crystallization of ZnFe2O4, so the wave absorbing performance is enhanced. When the temperature rises to 1023K, it can be seen from XRD analysis that the ZnFe2O4 in the product is partially decomposed to produce Fe x Zn y O phase, so the microwave absorption performance deteriorates.
[0082] Figure 7 is the R of the product at a specific thickness at different temperatures L The relationship between the thickness and the frequency. Lmin All of them move towards the low frequency direction. This phenomenon can be explained by the quarter-wavelength interference destructive theory, which means that there is electromagnetic interference type loss in the sample. In addition, it also shows that as the thickness of the sample increases, its absorption capacity in the low frequency band increases.
[0083] The three-dimensional Cole-Cole plot is drawn using ε′, ε″ and frequency, as shown in Figure 8 As shown in Equation 5 and Equation 6, if τ is constant, the values of and can be reduced by increasing the frequency f, which is consistent with Figure 8 The curve trends in (ab) remain consistent.
[0084]
[0085] Among them, ε′ and ε″ are the real and imaginary parts of the complex dielectric constant of the material, ε s and ε ∞ are the relative dielectric constant of the material when the frequency is close to 0 and the relative dielectric constant at infinite frequency, ω is the incident angle of the electromagnetic wave in radians, f is the frequency of the external alternating electromagnetic field, and τ is the relaxation time.
[0086] from Figure 8 It can be seen that the Cole curves of all samples are irregular shapes composed of multiple Debye semicircles in the medium and high frequency bands and "tail straight lines" in the low frequency band, indicating that the dielectric loss mechanism of the samples is composed of multiple dipole polarization relaxation and conduction loss. The Cole-Cole curves at temperatures of 823K and 873K are messy, and the Debye semicircle is not obvious, indicating that its polarization relaxation process is weak. With the increase of temperature, the curve trend gradually turns to clarity, and it can be clearly observed that the radius of the Debye semicircle increases significantly, indicating that the polarization relaxation effect of the product in the medium and high frequency bands is enhanced. When the temperature increases from 823K to 1023K, ε″ fluctuates between 0-0.10, 0.15-0.28, 0.30-0.70, 0.20-0.55 and 0.5-0.75, respectively, indicating that the electrical dissipation capacity of the product increases with the increase of temperature, which will also bring about the enhancement of the wave absorption performance, which is consistent with the Figure 6 Sample R L In summary, the increase in temperature will enhance the polarization relaxation effect of the product in the medium and high frequency bands.
[0087] Hysteresis loss is mainly caused by the time lag of the magnetization vector behind the external electromagnetic field vector, which is proportional to the area of the hysteresis loop and can be ignored. For spinel ferrites, exchange resonance occurs in the THz frequency range, and domain wall resonance usually only occurs in 1-100MHz. Therefore, in addition to natural resonance, eddy current loss may be another key magnetic loss mechanism that may exist in ZnFe2O4 powder in the GHz frequency range, which can be judged by calculating the C0 value (Equation 7).
[0088] C0=μ″(μ′) -2 ·f -1 Formula 7
[0089] μ′ and μ″ are the real and imaginary parts of the complex magnetic permeability, and f is the frequency.
[0090] In order to explore the effect of temperature on the magnetic loss mechanism of the product, the C0 values of the product in the range of 2-18 GHz at different temperatures were calculated. Fig. 9 As shown. At 823K, the C0 curve of the product decreases in the range of 2-3GHz, indicating that the magnetic loss mechanism is mainly natural resonance; it fluctuates slightly in the range of 3-18GHz, indicating that the magnetic loss mechanism is mainly eddy current loss. At 873-1023K, the C0 curves of the products first decrease and then maintain a stable trend, indicating that the magnetic loss mechanism of the sample is natural resonance and eddy current loss.
[0091] Fig.10 (a) is the af relationship curve of the product at different temperatures. In the entire frequency range, a increases with the increase of temperature, indicating that increasing the temperature can enhance the electromagnetic wave attenuation ability of the product. In the range of 2-8GHz, the a value of the product at 973K is greater than the α value of the product at 1023K, indicating that the electromagnetic wave attenuation ability of the product at 973K is stronger in this frequency range. This is because the ZnFe2O4 powder in the product at 1023K partially decomposes to produce Fe x Zn y O phase, reducing the content of ZnFe2O4 absorber.
[0092] Fig.10 (b) is the Zf curve of the product at different temperatures. In the low frequency range, as the temperature increases, Z max They are approximately 9.4, 4.8, 2.5, 1.1 and 1.5 respectively. It can be seen that increasing the temperature can optimize the impedance matching characteristics of the product. When the temperature is 973K, the Z value is closer to 1, indicating that the sample has a better impedance matching characteristic.
[0093] By analyzing the organizational structure, static magnetic properties, electromagnetic parameters, microwave absorption performance and loss mechanism of the products at different temperatures, it can be seen that the ZnFe2O4 grains at 973K have good crystallinity and dispersion, and have a large M s and the smallest R L , and obtain R Lmin In addition, the product has better electromagnetic wave attenuation ability and electromagnetic impedance matching characteristics among all samples, which provide conditions for obtaining better electromagnetic wave absorption performance. Therefore, the more preferred ball milling temperature is 973K.
[0094] (2) Characterization results of ZnFe2O4 absorbing materials prepared in Example 1 and Example 3
[0095] In order to explore the effect of ball milling time on the microstructure and electromagnetic properties of the product, the experiment was carried out at 973 K, with constant temperature ball milling for 4 h, 6 h, 8 h, 10 h and 12 h respectively.
[0096] Fig.11 The XRD diagrams of the products at different ball milling times are shown in the figure. The crystal planes corresponding to the characteristic peaks are marked in the figure. After 4h and 6h of ball milling, in addition to ZnFe2O4, the products also contain ZnO, Fe3O4 and Fe x Zn y O phase, indicating that the reaction was not complete under this condition. When the ball milling time was extended to 8h, 10h and 12h, the product was composed of ZnFe2O4 and ZnO. Comparing the diffraction peak intensity at the (311) crystal plane of ZnFe2O4 under different ball milling times, it first increased and then decreased with the extension of ball milling time. The product had the strongest crystallinity at 10h. This shows that appropriately extending the ball milling time is beneficial to the nucleation and growth of ZnFe2O4, but too long ball milling time leads to excessive accumulation of mechanical force, which inhibits the growth of ZnFe2O4 crystals.
[0097] Fig.12 The SEM images of the products at different ball milling times are shown below. The products are all spherical in structure, with a particle size distribution between 0-0.5 μm, and some agglomeration. As the ball milling time increases, the percentage of small-sized particles increases, and the degree of agglomeration first weakens and then increases. Fig.12 (ab) shows that a large number of spherical particles agglomerate into larger "particle clusters". From XRD analysis, it can be seen that although ZnFe2O4 is generated when the ball milling time is 4h and 6h, the reaction is not complete and there are still a large number of intermediate phases adhering together. Therefore, too short a ball milling time is not conducive to the formation and dispersion of ZnFe2O4. Extending the ball milling time to 8h and 10h weakens the agglomeration of the product particles. Continuing to extend the ball milling time to 12h, the agglomeration degree of the product particles intensifies and the size distribution is uneven. Too long a ball milling time will cause the product to undergo secondary crystallization, causing the particle size to grow abnormally, thereby deteriorating the performance of the product. Therefore, appropriately extending the time is conducive to the crystallization of the product particles and the reduction of agglomeration, and is also conducive to increasing the number of small-sized particles, thereby improving the performance of the product.
[0098] Fig.13 The hysteresis loops of the products at different ball milling times are shown in the typical "S" shape, indicating that the samples have soft magnetic properties. s 、M r and H c As shown in Table 2. s Both increase first and then decrease with the extension of ball milling time. The maximum M s The value is 44.94emu / g. From the SEM analysis above, we can see that when the ball milling time increases to 10h, the agglomeration of the product particles weakens with the extension of time, and the uniformly distributed particles enhance the M of the product.
[0099] Table 2 Static magnetic properties parameters of the products at different ball milling times
[0100] Time / h <![CDATA[M s / emu g -1 ]]> <![CDATA[M r / emu g -1 ]]> <![CDATA[H c / You]]> 4 22.13 0.14 6.93 6 27.03 0.53 10.40 8 29.16 0.77 13.68 10 44.94 3.94 76.01 12 27.22 0.62 19.43
[0101] Fig.14 (ab) are ε′ and ε″ of the products at different ball milling times. With the increase of time, ε′ and ε″ first increase and then decrease. ε′ fluctuates between 4.32-4.12, 4.45-4.10, 4.50-4.30, 4.71-4.23 and 4.85-4.31, respectively, while ε″ decreases from 0.22, 0.28, 0.47, 0.57 and 0.23 to 0.09, 0.19, 0.25, 0.21 and 0.09, respectively, indicating that appropriately extending the time is beneficial to improving the dielectric properties of the product. Too long a time may cause the product particles to agglomerate, which will have an adverse effect on its electrical storage and electrical loss capabilities.
[0102] Fig.14 (cd) are μ′ and μ″ of the products at different ball milling times. Among all the samples, the product at 10 h has the best μ′ and μ″ values, that is, it has the best magnetic loss performance, which can be regulated by the degree of particle agglomeration.
[0103] Fig.14 (ef) is the tanδe and tanδm of the products at different ball milling times. Within 10-18 GHz, the tanδe and tanδm of all samples are similar; within 2-10 GHz, tanδe < tanδm, and the tanδe and tanδm values of the products at 10h and 12h are much larger than those of the products at 4h, 6h and 8h. This shows that appropriately extending the ball milling time is beneficial to the improvement of magnetic loss capacity.
[0104] Fig.15 is the three-dimensional R of the product at different ball milling times L Fig. As the ball milling time increases, R Lmin The values of -6.6dB, -7.9dB, -13.2dB, -26.0dB and -20.4dB are respectively, and the corresponding thicknesses are 9.9mm, 9.9mm, 9.7mm, 7.6mm and 8.8mm. The absorption performance of the product first increases and then decreases. The reason for the different absorption performance may be that when the ball milling time is 4h and 6h, the raw material is not completely converted into ZnFe2O4, and there may be Fe in the product that affects the absorption performance. x Zn yO phase. As the ball milling time increases, a large amount of heat and mechanical energy is accumulated in the reaction process, which is conducive to the forward reaction, making the ZnFe2O4 crystal more complete and helping to provide excellent microwave absorption performance. When the ball milling time is further extended to 12h, the ZnFe2O4 crystal undergoes secondary crystallization and growth, resulting in abnormal growth of the particle size, which deteriorates the microwave absorption performance.
[0105] Fig.16 is the R of the product at a specific thickness under different ball milling times L The relationship between the thickness and the frequency. Lmin They all move toward the low-frequency direction, indicating that there is electromagnetic interference loss in the sample, and with the increase of thickness, the wave absorption ability of the sample in the low-frequency range is enhanced.
[0106] Fig.17 The Cole-Cole curves of the products at different ball milling times. The Cole curves of all samples are irregular shapes composed of multiple Cole semicircles in the medium and high frequency bands and "straight tails" in the low frequency bands, indicating that their dielectric loss mechanisms are composed of multiple dipole polarization relaxation and conduction loss. The Cole-Cole curves of the products in the medium and high frequency bands are chaotic when the ball milling time is 4h and 6h; as the time is extended to 10h, multiple Debye semicircles can be observed, and the radius increases significantly; when the time is extended to 12h, the curve gradually becomes chaotic. This shows that the polarization relaxation effect of the product first increases and then weakens. Among them, the polarization relaxation effect of the product is the strongest when the ball milling time is 10h. In addition, ε″ fluctuates between 0.08-0.22, 0.12-0.28, 0.25-0.50, 0.20-0.60 and 0.08-0.20, respectively. Therefore, with the extension of ball milling time, the electrical loss capacity of the product first increases and then decreases, which may lead to the strengthening and weakening of the microwave absorption performance. Fig.15 Middle to R L The analysis results are consistent.
[0107] Fig.18 The C0-f curves of the products at different ball milling times. As time increases to 8h, the C0 value decreases with the increase of frequency in 2-4GHz and tends to be stable in 4-18GHz, indicating that the magnetic loss mechanism of the product is natural resonance and eddy current loss in 2-4GHz and 4-18GHz, respectively. When the ball milling time is 10h and 12h, the C0 value decreases with the increase of frequency in 2-8GHz and remains stable in 8-18GHz, indicating that the magnetic loss mechanism at this time is natural resonance and eddy current loss in 2-8GHz and 8-18GHz, respectively.
[0108] Fig.19(a) is the curve of α of the product with different ball milling time and frequency. In the range of 2-18 GHz, α increases first and then decreases with the extension of ball milling time, reaching the maximum at 10 h, when the electromagnetic wave attenuation ability is the strongest. If the ball milling time continues to extend, a large amount of energy will accumulate inside the system, resulting in abnormal product particles and deterioration of electromagnetic wave attenuation ability.
[0109] Fig.19 (b) is the curve of Z of the product under different ball milling time and frequency. In the range of 2-18GHz, Z max The Z value of the product in the range of 2-6 GHz is closer to 1 when the ball milling time is 10 h, indicating that the impedance matching property is better under this condition.
[0110] In summary, the ball milling time has a significant effect on the product's organizational structure, static magnetic properties, electromagnetic parameters, microwave absorption performance and loss mechanism. Among them, the product with a ball milling time of 10 h has good crystallinity and dispersion, and has a large M s , the smallest R L and smaller thickness, and also has better electromagnetic wave attenuation ability and impedance matching characteristics, all of which provide conditions for obtaining better wave absorbing performance. Therefore, the ball milling time is selected as 10h.
[0111] (3) Characterization results of ZnFe2O4 absorbing materials prepared in Example 1 and Example 4
[0112] In order to explore the effect of the change of ball-to-material ratio on the product performance during the reaction process, the ball-to-material ratio was set to 5:1, 10:1, 15:1 and 20:1, the ball milling temperature was 973K, and the ball milling time was 10h.
[0113] Fig. 20 The XRD diagram of the product under different ball-to-material ratio conditions, the crystal plane corresponding to each characteristic peak is marked in the figure. The ZnO peak may come from the ZnO raw material volatilized during the high-temperature mechanical force process. As the ball-to-material ratio increases, the diffraction peak intensity of ZnFe2O4 first increases and then weakens, and reaches the strongest when the ball-to-material ratio is 15:1. It shows that a proper increase in the ball-to-material ratio is conducive to the crystallization of the product, but when the ball-to-material ratio is too large, it may amplify the collision between the grinding balls, weaken the mechanical effect of the grinding balls on the materials, reduce the ball milling efficiency, and inhibit the growth of ZnFe2O4 crystals.
[0114] Fig.21The SEM images of the products under different ball-to-material ratios are shown in the figure. It can be seen from the figure that the ball-to-material ratio can significantly affect the agglomeration degree and particle size distribution of the product. When the ball-to-material ratio is 5:1, the product has obvious agglomeration, which may be because there are too few grinding balls at this time, and the mechanical strength generated is not strong enough to make the product evenly distributed; when the ball-to-material ratio is increased to 10:1, the agglomeration of the product is weakened, but its particle size distribution is uneven, and large particles still exist; when the ball-to-material ratio is 15:1, the agglomeration is further weakened and the particle distribution is more uniform. This is because the appropriate ball-to-material ratio promotes the mechanical force of the ball milling media inside the system to enhance the material, resulting in an enhanced refinement and crushing effect; when the ball-to-material ratio continues to increase to 20:1, more obvious agglomeration and large particles appear in the product again. This is because the excessively large ball-to-material ratio enhances the interaction between the grinding balls and weakens their refinement and crushing of the material. In addition, as the ball-to-material ratio increases to 15:1, the average particle size of the product decreases and the percentage of particles in the small size range (0.2-0.3μm) increases; when the ball-to-material ratio is 20:1, the average particle size of the product increases to about 0.3μm, and the number of small-sized particles decreases.
[0115] Fig. 22 The hysteresis loops of the products obtained with different ball-to-material ratios are shown in Figure 2. All samples have an S-shaped hysteresis loop, indicating that they have soft magnetic properties. The corresponding M s 、M r and H c As shown in Table 3. s As the ball-to-material ratio increases, it first increases and then decreases. When the ball-to-material ratio is 15:1, M s The maximum value is 44.94emu / g. According to the SEM analysis in the previous article, as the ball-to-material ratio increases from 5:1 to 15:1, the agglomeration of the product weakens, and the uniformly distributed magnetic particles lead to the M s However, when the ball-to-material ratio is too large (20:1), the interaction between the grinding balls weakens the refinement and crushing of the materials, resulting in agglomeration and an increase in the product particle size, thereby reducing the M s .
[0116] Table 3 Static magnetic properties parameters of samples prepared under different ball-to-material ratios
[0117] Ball to Material Ratio <![CDATA[M s / emu g -1 ]]> <![CDATA[M r / emu g -1 ]]> <![CDATA[H c / You]]> 5∶1 3.63 0.02 1.50 10∶1 13.01 0.09 6.16 15∶1 44.94 3.96 74.51 20∶1 15.76 0.04 1.42
[0118] Fig.23(ab) are ε′ and ε″ of the products obtained under different ball-to-batch ratios. As the ball-to-batch ratio increases, the ε′ and ε″ values first increase and then decrease, and both decrease with increasing frequency. This is because the increase in the ball-to-batch ratio leads to an increase in the strength of the mechanical force provided in the system, which helps to disperse the product particles, thereby weakening the agglomeration. The evenly distributed particles help to transport internal free electrons, thereby enhancing its dielectric properties. When the ball-to-batch ratio is too large (20:1), it will lead to increased agglomeration, which is not conducive to the transport of free electrons inside the material, thereby adversely affecting the product's electrical storage and electrical loss capabilities, resulting in a decrease in ε′ and ε″ values.
[0119] Fig.23 (cd) are μ′ and μ″ of the products obtained under different ball-to-batch ratios. When the ball-to-batch ratio is 5:1, μ′ of the product fluctuates greatly with frequency, and μ″ decreases sharply first and then remains stable with the increase of frequency; when the ball-to-batch ratio is 10:1, 15:1 and 20:1, μ′ and μ″ fluctuate less with frequency and the change trend is consistent, which indicates that the magnetic loss performance of the product when the ball-to-batch ratio is 5:1 is more sensitive to frequency changes, while the frequency change has little effect on the magnetic loss performance of the product when the ball-to-batch ratio is 10:1, 15:1 and 20:1.
[0120] Fig.23 (ef) is the tanδe and tanδm of the products obtained under different ball-to-batch ratios. As the ball-to-batch ratio increases, the dielectric loss performance of the product first increases and then decreases, reaching the maximum when the ball-to-batch ratio is 15:1. For the product with a ball-to-batch ratio of 5:1, tanδe>tanδm exists in the range of 2-8GHz, while the tanδe and tanδm values are not much different in the range of 8-18GHz, indicating that its loss mechanism is mainly dielectric loss in the range of 2-8GHz, while there is a synergistic effect of dielectric loss and magnetic loss in the range of 8-18GHz. The tanδe and tanδm values of the products with ball-to-batch ratios of 10:1, 15:1 and 20:1 are not much different in the range of 2-18GHz, indicating that the loss mechanism of the product at this time is the synergistic effect of dielectric loss and magnetic loss.
[0121] Fig.24 is the three-dimensional R of the product under different ball-to-material ratio conditions L Figure. When the ball-to-material ratio increases from 5:1 to 15:1, R Lmin From -13.2dB to -26.0dB, the corresponding matching thickness is reduced from 9.7mm to 7.6mm. Continue to increase the ball-to-material ratio to 20:1, R LminThe ratio of ball to material is reduced to -22.4dB, and the matching thickness is increased to 10mm. Therefore, as the ball to material ratio increases, the wave absorption performance of the product first increases and then weakens. This is because when the ball to material ratio is small, the grinding balls in the system cannot provide enough mechanical force, which causes the product to agglomerate and thus affects its conductivity, which in turn has an adverse effect on its wave absorption performance; when the ball to material ratio increases to 15:1, sufficient mechanical force avoids the agglomeration of product particles, optimizes its dielectric properties, and improves the wave absorption performance of the product.
[0122] Fig.25 The relationship curve between RL and frequency of products under different ball-to-material ratio conditions at a specific matching thickness. As the matching thickness increases, the R Lmin All of them move toward the low-frequency direction, indicating that all samples have better wave-absorbing performance in the low-frequency band.
[0123] Fig.26 The three-dimensional Cole-Cole diagram of the product under different ball-to-material ratio conditions. The Cole curves of all samples are irregular shapes composed of multiple Cole semicircles in the medium and high frequency bands and a "straight tail" in the low frequency band, indicating that the dielectric loss mechanism of all samples is composed of multiple dipole polarization relaxation and conduction loss. ε″ fluctuates between 0.2-0.55, 0.25-0.5, 0.4-1.1 and 0.3-0.8, respectively. Therefore, with the increase of the ball-to-material ratio, the electrical dissipation capacity of the product first increases and then weakens, that is, the polarization relaxation effect in the medium and high frequency bands first increases and then weakens. The polarization relaxation effect of the product is the strongest when the ball-to-material ratio is 15:1, which is consistent with the Fig.24 Middle to R L The analysis results are consistent with .
[0124] Fig. 27 The C0-f curves of the products under different ball-to-metal ratios are shown in Figure 2. The C0 values of the products when the ball-to-metal ratio is 10:1 and 20:1 remain stable within 2-18 GHz, indicating that the magnetic loss mechanism of the samples at this time is mainly eddy current loss. For the products when the ball-to-metal ratio is 5:1 and 15:1, their C0 values decrease with the increase of frequency within 2-6 GHz and 2-10 GHz, respectively, and remain stable with the increase of frequency within 6-18 GHz and 10-18 GHz, indicating that the magnetic loss mechanism of the samples when the ball-to-metal ratio is 5:1 within 2-6 GHz and 6-18 GHz is mainly natural resonance and eddy current loss, respectively; the magnetic loss mechanism of the samples when the ball-to-metal ratio is 15:1 within 2-10 GHz and 10-18 GHz is mainly natural resonance and eddy current loss, respectively.
[0125] Fig.28(a) is the curve of α changing with frequency under different ratios of ball to material. In the range of 2-9GHz, α reaches the maximum when the ratio of ball to material is 15:1; in the range of 9-18GHz, the α value of the product with the ratio of ball to material is 15:1 is lower than the α values of the products with the ratio of ball to material is 5:1 and 10:1, indicating that the attenuation ability of the product with the ratio of ball to material is weaker than that of the product with the ratio of ball to material is 5:1 and 10:1 in the high frequency band.
[0126] Fig.28 (b) is the curve of the Z of the product under different ball-to-material ratios as a function of frequency. In the entire frequency range, the Z of each ball-to-material ratio max They are about 3.8, 4.0, 2.5 and 3.3 respectively. When the ball-to-material ratio is 15:1, the Z value in the range of 3-6GHz is closer to 1, indicating that the product under this condition has the most suitable impedance matching characteristics.
[0127] Through the analysis of the organizational structure, static magnetic properties, electromagnetic parameters, wave absorption performance and loss mechanism of the products under different ball-to-material ratio conditions, it can be seen that when the ball-to-material ratio is 15:1, the grains of the product have good crystallinity and dispersion, and have a large M s and the smallest R L , and at the same time, obtain R Lmin The corresponding matching thickness is smaller. In addition, the product under this condition has better electromagnetic wave attenuation ability and electromagnetic impedance matching characteristics, which provide conditions for obtaining better wave absorbing performance. Therefore, the ball-to-material ratio is selected as 15:1.
[0128] (4) The properties of the ZnFe2O4 absorbing materials prepared in Example 1 and Comparative Examples 1-2 are shown in Table 4.
[0129] Table 4 Performance test results of ZnFe2O4 absorbing materials of Example 1 and Comparative Examples 1-2
[0130]
[0131] Therefore, the present invention adopts a method for preparing a ZnFe2O4 absorbing material with the above structure, and the prepared ZnFe2O4 material has excellent absorbing performance.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a ZnFe2O4 absorbing material, characterized in that: The following steps are involved: (1) mixing zinc oxide powder and ferric oxide powder to obtain a mixed powder; (2) The mixed powder and grinding balls are added into a ball mill, and then loaded into a high-temperature energy ball mill for ball milling. After the ball milling is completed, the ZnFe2O4 absorbing material is obtained.
2. The method for preparing a ZnFe2O4 absorbing material according to claim 1, characterized in that: The molar ratio of zinc oxide powder to ferric oxide powder in step (1) is 1:(2-2.2).
3. The method for preparing a ZnFe2O4 absorbing material according to claim 1, characterized in that: The grinding balls in step (2) are zirconia grinding balls, and the zirconia grinding balls include zirconia grinding balls with a diameter of 8 mm and zirconia grinding balls with a diameter of 16 mm in a mass ratio of 1:(2-2.5).
4. The method for preparing a ZnFe2O4 absorbing material according to claim 1, characterized in that: The mass ratio of the mixed powder to the grinding balls in step (2) is 1:(5-20).
5. The method for preparing a ZnFe2O4 absorbing material according to claim 1, characterized in that: The ball mill in step (2) is made of 2520 stainless steel, with an inner diameter of 165 mm, an outer diameter of 170 mm, and a height of 150 mm.
6. The method for preparing a ZnFe2O4 absorbing material according to claim 1, characterized in that: In step (2), the ball milling temperature is 773~1023K, and the heating rate is 4K·min -1 , the rotation speed is 30~50rpm.
7. The method for preparing a ZnFe2O4 absorbing material according to claim 1, characterized in that: The ball milling time in step (2) is 4 to 12 hours.